Narrativa de las demandas escolares y estrategias de afrontamiento frente al estrés por un grupo de estudiantes de educación secundaria de los grados décimo y once. (2024)
The objective of this research is to explore, identify and define school demands, narrated as stressors and coping strategies implemented in a group of high school students, specifically in tenth and eleventh grades of a private school in the city of Bogota. In this sense, it deepens on the subject of academic stress from the cognitive-scitivist systemic model of academic stress and from the narrative that the students have.